The Influence of Flower Anatomy and Apple Cultivar on the Apple Flower Phytobiome - Blaire Steven; Regan B. Huntley; Quan Zeng (2018)
The apple flower is a transient organ that can shed light on how plant-associated phytobiomes are established and structured. Stigmas, stamens, receptacles, and petals were dissected from flowers, and the microbiome of each structure was characterized. Each flower part harbored a largely overlapping set of bacterial taxa, predominantly within the groups Pseudomonas and Enterobacteriaceae. However, the structure of the communities differed. The stigmas showed a high dominance of a small number of operational taxonomic units (OTUs; 97% sequence identity) whereas OTUs on petals were more even in relative abundance. Results from the OTU analysis of phytobiomes from stigmas from three apple cultivars, Braeburn, McIntosh, and Sunrise, indicated cultivar did not significantly influence community structure. Correlation analysis of bacterial taxa in the apple phytobiome found a negative correlation between Pseudomonas and Enterobacteriaceae, suggesting a potential niche exclusion relationship between these taxa. In this respect, the phytobiome of the apple flower is relatively simple but different flower parts, particularly the stigma, enrich the relative abundance of specific bacterial populations. Correlations in the community structure point to potential antagonistic relationships, which could be used to manipulate the structure of the microbiome for biological control of pathogens or other orchard management strategies.